CONSUMERS’ OPİNİONS TOWARDS GENETİCALLY MODİFİED FOODS: A CROSS-CULTURAL COMPARİSON (Third Sector Social Economic Review, 2011)
This research was planned and carried out to determine the opinions towards genetically modified foods of university student consumers’ who came from different cultures. From Maryland University of United States of America (n=120) and Ankara University of of Turkey (n=120) totally 240 university student consumers included into study. In gathering the research materials was used to questionnaire technique In this research, the khi-kare analysis was performed for determining the differences dependent on country related to consumers’ opinions towards genetically modified foods. The results of khi-square analysis related to genetically modified foods showed that the state of willing to try the new food products and genetically modified foods appear on the market, consuming genetically modified foods without knowing it, discovering that eating genetically modified foods change this situation. The most important benefit out of genetically modified foods trade, the main reason for choosing genetically modified foods, the most important possibleeconomical benefit of genetically modified foods, being all types of genetically modified foods are benefitable/economical for consumer (p
Keywords: Consumer; genetically modified food; opinion